MULTIMODALITY IMAGING APPROACH FOR THE EARLY DIAGNOSIS BOERHAAVE SYNDROME - Anwar, Javed; Maqsood, Rasikh; Soomro, Sanaullah (Journal of Ayub Medical College Abbottabad, 2017)
Boerhaave's syndrome is a spontaneous transmural rupture or perforation of the oesophagus or post-emesis oesophageal rupture. Boerhaave's syndrome has a high risk of morbidity and mortality, and early, definitive diagnosis leading to prompt management improves outcomes. Definitive diagnosis of this syndrome is made with imaging, including x-ray, USG and computed tomography Scan. This is a case of a 50-year male with history of sudden onset of epigastric pain after an episode of forceful emesis was referred for Ultrasound (USG) abdomen. His USG examination demonstrated fluid collection with internal free floating and linear echoes in left pleural cavity consistent with hemo-pneumothorax his further imaging workup was done with suspicious of Boerhaave's Syndrome which conformed the suspected diagnosis. Keywords: Boerhaave's Syndrome; Pneumomediastinum; Oesophagus